PENGARUH POROSITAS PACKING STEEL WOOL TERHADAP PRESSURE DROP DIDALAM PACKED BED COLUMN PADA DISTILASI CAMPURAN ETANOL-AMIL-ALKOHOL-AIR - Trisna Kumala Dhaniswara; Tri Widjaja; Ali Altway (Journal of Research and Technology, 2016)
Inventories of petroleum fuels are increasingly depleted and will someday run out. These shortcomings can be overcome by using alternative fuels, such as ethanol. Based on this, it is necessary to research and development of ethanol as a fuel. One way is with a separation in a packed distillation column. This study aims to assess the mass transfer phenomena that occur in the process of distilling a mixture of ethanol-water-amyl alcohol packed in column. In addition, this study aims to optimize temperature and reflux to obtain the highest levels of ethanol. This research method uses packed bed distillation system with the batch process. Feed used is synthetic ethanol, water, and solvent. Solvent used were amyl alcohol. Doing distillation with heating temperature is maintained. Distillation is done in the packing of stainless steel wool. Research carried out in a batch process with a variable temperature of 79°C; 84°C; 91°C; and porosity packing 20%; 30%; 40%; 50%; 60%; 70%; 80%.